Analisis Fenomena Pemukulan terhadap Siswa Yaredi Ndruru oleh Kepala Sekolah SMKN 1 Siduaori-Nias Selatan: Kajian Filsafat Manusia - Hermanus Ndode; Yosef Usman; Benyamin Guido Reke (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
In the context of the phenomenon of the beating of students such as that of Yaredi Ndruru by the Principal of SMKN 1 Siduaori-South Nias, the study of human philosophy plays an important role in unraveling the background, causes and implications of such actions. This phenomenon reflects the complex relationship between individuals, power and social norms in the context of education. Human philosophy analysis encourages us to question the essence of humanity, ethics and moral responsibility held by individuals, especially those with power such as a principal. Battering as a physical act raises questions about the limits of power and human rights, and highlights inequalities in teacher-student relationships. Furthermore, it considers the psychological and emotional impact on victims of beatings as well as the long-term consequences on students' self-confidence and motivation to learn. Philosophical considerations also question whether such actions are a result of the education system's failure to promote values such as empathy, respect and dialogue as means of conflict resolution. Thus, analyzing the phenomenon of the beating of student Yaredi Ndruru by the Principal of SMKN 1 Siduaori-South Nias from the perspective of human philosophy opens up space for deep reflection on human values in the context of education as well as the urgency of protecting individual rights in the school setting.